Análise não linear de chapas através de uma formulação do método dos elementos de contorno com convergência quadrática - Dóro, Vinício da Cunha [UNESP] (2015)
In this paper the linear formulation of the boundary element method (BEM) for analyzing the stretching plate problem written in terms of displacements and tractions in the normal and tangential directions to the boundary has been developed. The integral equation of displacement is derived from Betti's reciprocity theorem, considering constant thickness on the plate. Then the BEM nonlinear formulation has been obtained by considering an initial (or inelastic) force field over the plate domain, requiring therefore the plate domain discretization into cells. The nonlinear solution is obtained by an implicit formulation, where the strains correction to be computed for each iteration is obtained by considering the consistent tangent operator, leading to a quadratic convergence rate in the iterative procedure required to achieve the plate equilibrium. In the numerical examples, the Von Mises criterion has been adopted to model the material behavior, showing the quadratic convergence rate. Besides different discratizations have been analyzed in order to show as well the results convergence